2001
DOI: 10.1111/j.1349-7006.2001.tb01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Receptor and Vascular Endothelial Growth Factor Are Synergistically Associated with the Liver Metastasis of Colorectal Cancer

Abstract: Considering recent findings that the urokinase plasminogen activation (PA) system is involved in invasion and vascular endothelial growth factor (VEGF) is involved in angiogenesis of colorectal cancer, we evaluated these factors in the liver metastasis of primary colorectal cancer. Cancer tissues from 71 colorectal cancer patients were assayed quantitatively for antigen levels of urokinase type plasminogen activator (uPA), uPA receptor (uPAR), and plasminogen activator inhibitor-1 and -2 (PAI-1, PAI-2), and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…This is the fi rst study to show quantitatively that IL-8 was correlated with PA system factors, uPA, uPAR, and PAI-1 in CRC. A positive correlation between VEGF overexpression and both uPAR expression and liver metastasis was demonstrated in our previous study [29] . In the present study, the VEGF level was quantitatively correlated with the levels of uPAR and PAI-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the fi rst study to show quantitatively that IL-8 was correlated with PA system factors, uPA, uPAR, and PAI-1 in CRC. A positive correlation between VEGF overexpression and both uPAR expression and liver metastasis was demonstrated in our previous study [29] . In the present study, the VEGF level was quantitatively correlated with the levels of uPAR and PAI-1.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the existence of a relationship between VEGF and the PA system, which promote angiogenesis synergistically in CRC [29] . In this context, we investigated the relationship of IL-8 with VEGF and PA system factors in CRC.…”
mentioning
confidence: 99%
“…Increased uPA and uPAR expression in tumor cells is correlated with advanced disease, shorter survival time, and increased frequency of liver metastasis, thus supporting a role for the uPA system in tumor invasion [9][10][11][12][13][14][15]. The signaling mechanisms that regulate uPA and uPAR expression are not fully characterized but may involve the Ras/ERK, TGF-β, and Wnt signaling pathways [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In both tumor tissue and blood, high uPAR concentrations have been shown to correlate with a poor prognosis in several types of cancer (8 ). The use of immunoassays that measure a combination of different uPAR forms has demonstrated that uPAR concentrations in extracts of tumor tissue samples from CRC patients are an independent prognostic factor for 5-year overall survival (9 ), and there are indications that uPAR concentrations correlate with liver metastasis (10 ). The plasma suPAR concentration has also been correlated with survival in CRC patients (11 ).…”
mentioning
confidence: 99%